Sorption efficiency of kaolinte in removal Cd from aqueous solutions - Muhammad Awadh, Salih; Hameed Yousif, Ayad Abdul (Iraqi Journal of Science, 2023)
Because of the contaminants represented by heavy metals in the aquaticenvironment have an adverse effects need to be addressed, therefore, a laboratorysimulation was conducted on Cd using kaolinite that collected from Ga’ara Formationas considered as a natural sorbent material that can be used to remove heavy metalsfrom aqueous environments. Mineralogical study was conducted on kaolinite usingX-Ray diffraction (XRD), Scanning Electron Microscope (ESM) and Energy-Dispersive X-ray Spectroscopy (EDS) for the purpose of investigating the microtexture.It was found that kaolinite has pure phase of very fine grains with a very littlequantity of quartz and has a number of active sites for adsorption. Chemical analyzeswere performed using atomic absorption spectroscopy (AAS), Electron Probe Microanalyzer (EPMA) and Energy-Dispersive X-ray Spectroscopy (EDS) techniquesconfirmed a purity of kaolinite due to high alumina content, except a rare slica contentoriginated from quartz. Kaolinite sorption efficiency was investigated through a seriesof laboratory experiments. The optimal reaction conditions were determined to be as:pH 5 to 9, but the best is 9, and the eqilibrium reaction time is 40 minutes, and thesolid to liquid ration is 1.25 gm to 50 ml. The effect of the initial Cd concentration onthe sorption efficiency of kaolininte was also investigated and shows that the sorptionproportionally increases with high concentration. All the laboratory experimentsindicate that the reaction is an indothermic.